Efektivitas Spiritual Emotional Freedom Technique (SEFT) terhadap Self Confidence Mahasiswa Eks Pesantren IAIN Tulungagung - Uswah Wardiana; Mirna Wahyu Agustina (Program Studi Psikologi Islam (IAIN) Kediri, 2021)
Spiritual Emotional Freedom Technique (SEFT) is a therapeutic technique that combines spiritual and psychological elements in practice. The life of pesantren which is closely related to spirituality is one of the bases for the selection of SEFT techniques as a step to increase the confidence of former pesantren students. The aim of the study is directed at overcoming the inferiority problems of ex pesantren students caused by stress. The research method used is quantitative research. The form of treatment given to study participants was Spiritual Emotional Freedom Technique (SEFT) therapy. The design / perspective of this study used SEFT experimental therapists with subjects namely ex-Islamic boarding school students from Tulungagung IAIN with an experimental approach to pre-test post-test with control group experimental design. The number of subjects who participated was 90 ex-pesantren students at IAIN Tulungagung. SEFT therapy techniques can significantly increase self-confidence with a significance value of 0.001 (p <0.05) and t value = 6.891.